SUSTAINABILITY ACCOUNTING IMPLEMENTATION IN HIGHER EDUCATION INSTITUTIONS: REFLECTION FROM UI GREENMETRIC RANKING - Kurniawan, Putu Sukma; Dewi, Luh Gede Kusuma (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study aims to identify sustainability accounting practices in Indonesia's higher education institutions (HEIs) and develop future recommendations. This study analyses reports and data from Indonesian universities ranked in UI GreenMetric. The recommendations are based on the data analysis stages. The findings indicate that a relatively small number of HEIs have adopted sustainability accounting practices. The study results have highlighted significant issues about sustainability accounting in HEIs, and recommendations have been proposed for future implementation. The findings of this study can inform the future implementation of sustainability accounting at the university level, providing a helpful reference point for university management and relevant stakeholders. This study aims to offer a novel perspective on the potential integration of sustainability accounting practices, particularly within the context of HEIs. Ultimately, the study aims to position sustainability accounting as a central tool for HEIs to transition toward more sustainable, transparent, and accountable practices and transform into the sustainable university.